Asymmetric Preparation of New N,N-Dialkyl-2-amino-1,1,2-triphenylethanol Catalysts and a Kinetic Resolution in the Addition of Diethylzinc to Flavene-3-carbaldehydes - Kang, Seock Yong; Baek, Jinho; Ko, Yi Kyung; Im, Chan; Park, Yong Sun (Synlett, 2013)
Enantiopure N,N-dialkyl-(S)-2-amino-1,1,2-triphenylethanols were prepared using a new synthetic methodology and tested for their ability to catalyze the enantioselective addition of diethylzinc to aldehydes. The structural modification of N-substituents of the catalysts led us to identify N-methyl-N-(S)-1-phenylethyl-substituted 4d as an effective catalyst for the addition. Also disclosed is a kinetic resolution of racemic flavene-3-carbaldehydes with the chiral catalyst.
Keywords: addition; asymmetric catalysis; chirality; enantioselectivity; kinetic resolution